Acellular Fish Skin Grafts and Pig Urinary Bladder Matrix Assessed in the Collagen-Induced Arthritis Mouse Model. (December 2018) - Magnusson, Skuli; Kjartansson, Hilmar; Baldursson, Baldur Tumi; Astradsdottir, Katrin; Ågren, Magnus S.; Hilmarsson, Hilmar; Sigurjonsson, Gudmundur Fertram
It is vital that cellular- and tissue-based products (CTPs) used for wound treatment do not provoke autoimmunity. In this study, the immunogenic response to extracts of 2 CTPs of piscine and porcine origin was assessed in the collagen-induced arthritis model. Male DBA/1J mice were divided into 4 groups, each composed of 7 to 9 animals. Each animal was injected with one of following to assess their immune responses: (1) bovine type II collagen (100 µg) in Freund's adjuvant, (2) extract of piscine skin (100 µg) in Freund's adjuvant, (3) extract of porcine urinary bladder matrix (100 µg) in Freund's adjuvant, or (4) Freund's adjuvant alone (control) at the beginning of the experiment and 3 weeks later. Clinical signs of arthritis were assessed from week 5 onwards, and anti-type II and anti-type I collagen antibody immunoglobulin G (IgG) serum levels were measured before injections and 8 weeks after exposure using enzyme-linked immunosorbent assays. Only the mice exposed to bovine type II collagen developed clinical arthritis accompanied by very high anti-type II collagen IgG serum levels. Anti-type II collagen IgG serum levels were also detected in the porcine group but were undetectable in the piscine skin and control groups after 8 weeks. There were no significant differences in anti-type I collagen IgG serum levels among the groups. The results showed that piscine skin did not provoke systemic autoimmunity against type II collagens in DBA/1J mice.